Effects of Health Qigong Exercise on Lower Limb Motor Function in Parkinson's Disease - Li, Xiying; Lv, Chuanfen; Liu, Xiaolei; Qin, Xia (Frontiers in Medicine, 2022)
Purpose: This study explored the effects of Health Qigong exercise on lower limb motor function in Parkinson’s disease (PD) patients. Patients and methods: The experimental group completed an intervention of Health Qigong exercise over 12 weeks while the control group did not perform any regular physical activity. Data relating to gait, lower-limb joint range of motion, Timed Up and Go, as well as scores for motor function scale from the Unified Parkinson’s Comprehensive Rating Scale III before and after the intervention were collected for Repeated Measure Analysis of Variance. Results: Compared to the control group, Health Qigong exercise improved patients’ constant- and high-speed stride length and gait velocity, but not constant- and high-speed stride frequency. Left and right hip flexion and extension range were improved, as well as left and right knee flexion range. Finally, Timed Up and Go time became significantly slower, and Unified Parkinson’s Comprehensive Rating Scale III score significantly decreased. Conclusion: Health Qigong exercise can improve walking ability and lower limb joint range of motion in PD patients, lessen motor difficulties, and improve the quality of life. This non-pharmacological exercise intervention may be a useful adjustment treatment for Parkinson’s disease.